THE TUBE HADIS STUDY ABOUT MONOPOLY IN BUSINESS ECONOMY - Nurhadi Nurhadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
Abstract: Islam is a comprehensive religion that encapsulates all human life including economic activities. Economic and business activities may not or are prohibited from monopolizing goods that are needed by society. In this study will examine the prohibition of monopoly in the Al-Tis'ah polar hadith book. So the result was that the researchers found hadiths related to business monopoly as many as 49 hadiths in the nine, namely Bukhari No. 1319, 2532, 2558, 2565, 2570, 6695, Muslim No. 2790, 3012, 3013, Abu Daud No. 1727, 2990, Tirmizi No. 1188, 2136, 2137, 3353, 3438, Ibn Majah No. 1777, 2144, 2145, 2146, 2464, Ahmad No. 130, 3481, 4379, 4648, 4932, 7217, 7886, 7946, 8263, 8998, 11619, 12313, 12424, 12491, 12705, 12952, 12967, 13124, 13438, 13561, 12967, 13124, 13438, 13561, 15201, 20288, 20478, 20497, 20511, 20548 and Al-Darimi No. 2431, 2432. Bukhari Hadith No. 1319 is in the Book: Zakat, Chapter: Assets That Have Been Issued by Zakat Are Not Considered As Hoarding Treasure, No. Hadith: 1319. Muslim Hadith No. 2790 is in the Book: Buying and selling, Chapter: A ban on someone doing a sale and purchase transaction on another person's transaction, No. Hadith: 2790. Hadith Abu Daud No. 2990 is in the Book: Buying and selling, Chapter: Prohibition to hoard, No. Hadith: 2990. Hadith Tirmizi No. 1188 is in the Book: Buying and selling, Chapter: Hoarding, No. Hadith: 1188. Hadith Ibn Majah No. 2464 is in the Book: Laws, Chapters: Muslims unite in three things, No. Hadith: 2464. Hadith Ahmad No. 130 in the Book: Musnad ten friends guaranteed to enter heaven, Chapter: The beginning of the musnad of Umar bin Al-Khatthab Ra, No. Hadith: 130. Hadith Al-Darimi No. 2431 is in the Book: The book of buying and selling, Chapter: Prohibition of hoarding, No. Hadith: 2431. Keywords: Hadith Study, Kutub Al-Tis'ah, Monopoly, Business Economy